Metabolic syndrome and its associated factors among type 2 diabetic patients in Mizan-Tepi University Teaching Hospital, Southwest Ethiopia Region - Shita, Abel; Teshome, Habtamu; Ayalew, Mulugeta; Yesuf, Wudu; Getachew, Dawit (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Patients with diabetes mellitus (DM) are prone to modifiable and non-modifiable complications, which can be grouped under metabolic syndrome (MetS). Evaluating MetS in patients with diabetes is critical for the prevention of cardiovascular disease among patients with DM. In Ethiopia, more specifically in the southwest of Ethiopia, these kinds of information are lacking. Thus, this study estimated the prevalence of metabolic syndrome among type 2 diabetic patients and its associated factors. Methods A health facility-based cross-sectional study was done from May 1 to 30, 2021. The data were collected using structured questionnaires, laboratory investigations, and anthropometric measurements. MetS was diagnosed using the modified International Diabetic Federation guidelines (IDF) and the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. The data was entered into Epidata and analyzed using SPSS software. Bivariable and multiple variable logistic regression was done to identify the factors associated with MetS. In multiple-variable logistic regression analysis, variables that have a p-value ≤ 0.05 were declared to have statistical significance. Result The majority (31.4%) of study participants were within the age group of 41-50 years and the mean ± SD of age is 51.75 ± 11.66, and 54.9% of them were men. In this study, the prevalence of MetS was 31.4% and 41.2% using the IDF and NCEP-ATP III criteria, respectively. Being a woman (AOR = 11.33, 95% CI; 3.73, 34.34; p < 0.001), having a lower level of education (AOR=7.10, 95% CI; 1.88, 26.70; p <0.004), and performing high physical activities (AOR=0.08, 95%CI; 0.01, 0.40; p <0.002) were significantly associated with MetS. Conclusion According to this study, the magnitude of Metabolic Syndrome in Mizan-Teppi University Teaching Hospital was 31.4% and 41.2% using IDF and NCEP-ATP III criteria, respectively. Being a woman and having a lower level of education increased the odds of MetS among patients with DM while performing high physical activities decreased the odds of MetS among patients with DM. Therefore, to prevent metabolic syndrome among type 2 DM patients in the study area, it is crucial to focus on women and individuals who have not had access to adequate education. One way to do this is by prioritizing interventions that involve physical activity.